Pain associates with subjective memory problems and cognition in older Puerto Rican adults. Issue 6 (2nd November 2022) - Bell, Tyler Reed; Pope, Caitlin N.; Downer, Brian; Barba, Cheyanne; Crowe, Michael
ABSTRACT: This study examined whether pain is associated with subjective memory problems or cognition in Puerto Rican older adults. Participants came from the Puerto Rican Elderly Health Conditions (PREHCO) study, aged 60 and over ( n = 2, 144). Analyses examined concurrent and longitudinal associations of pain with subjective memory problems and cognition using a cognitive screener. Overall, participants with pain were more likely to report concurrent subjective memory problems than those without pain. Older adults with pain also exhibited slightly lower concurrent cognition. Novel pain was associated with cognitive decline and greater likelihood of incident subjective memory problems at follow-up. Persistent pain was only related to incident subjective memory problems at follow-up. Pain is associated with cognitive decline and subjective memory problems in older Puerto Ricans. Future studies should implement more in-depth neuropsychological assessments and examine the potential role of barriers to pain management in this population.